Effectiveness of Immersive Virtual Environments in Learning 3D Transformations in Computer Graphics and Impact on Spatial Skills - Alobaid, Maha Abdulaziz (Trinity College Dublin. School of Computer Science & Statistics. Discipline of Computer Science, 2026)
With the rapid advancements in virtual reality technology, new opportunities are emerging for enhancing learning experiences, particularly in disciplines that require strong spatial reasoning. However, it remains unclear to what extent immersive virtual environments can influence students' spatial skills, especially in complex subjects such as 3D transformations in computer graphics. This study explores the role of immersive virtual reality in improving spatial skills by evaluating its effectiveness in teaching 3D transformations through visual and interactive experiences. Over the course of several studies, our research has gradually honed in on the impact of immersive virtual environments on students' understanding of spatial concepts. Initially, the focus was on user engagement and satisfaction with virtual systems. As the research progressed, it became evident that the immersive nature of virtual reality and its interactive capabilities played a crucial role in improving spatial reasoning. Through a combination of pilot studies, one-group pretest-posttest designs, and expert evaluations, this work identifies how immersive virtual systems provide significant affordances for visual learning and interaction with 3D transformations. This thesis presents findings that suggest immersive virtual environments, by allowing students to manipulate and visualize 3D objects from multiple perspectives, enhance their spatial skills more effectively than traditional methods. Furthermore, the study investigates how expert evaluations of virtual effectiveness align with user experiences, ultimately highlighting the value of immersive virtual reality as a tool for teaching spatial reasoning in computer graphics. The results point to the potential of virtual reality not just as an educational tool but as a platform to reshape the way spatial learning is approached, particularly in STEM education.
APPROVED
Keywords: Computer Graphics; 3D Transformations; Virtual Reality; Immersive Virtual Environment; Spatial Skills; Spatial Visualization Skills; CTML